2017
DOI: 10.1007/s11252-017-0702-1
|View full text |Cite|
|
Sign up to set email alerts
|

Wellbeing and urban living: nurtured by nature

Abstract: In recent decades, empirical evidence has demonstrated that nature can enable urban environments to support human wellbeing. Research into links between nature and human wellbeing is often carried out with one wellbeing index or in single locations, which can limit our understanding of findings. To further this work, we deployed an online survey to residents of the two most-populous cities in both Australia and New Zealand. The survey measured self-reported wellbeing via three indices used widely in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Our finding that more greenery correlates positively with mental health and wellbeing corresponds with findings reported elsewhere [6,25,27]. [13] observed that while NDVI was positively associated with wellbeing for two Australian cities, this was not the case for two cities in New Zealand. The latter also corresponds to a Dutch study on psychotic disorders [11].…”
Section: Main Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that more greenery correlates positively with mental health and wellbeing corresponds with findings reported elsewhere [6,25,27]. [13] observed that while NDVI was positively associated with wellbeing for two Australian cities, this was not the case for two cities in New Zealand. The latter also corresponds to a Dutch study on psychotic disorders [11].…”
Section: Main Findingssupporting
confidence: 92%
“…The outcome measure was respondents' mental wellbeing. To quantify a multi-dimensional construct like subjective psychological wellbeing, we applied the World Health Organization Well-Being Index (WHO-5) [40], which had previously been implemented in greenery studies [8,13]. The questionnaire comprises five items evaluating respondents' mental health-related feelings over the previous two weeks.…”
Section: Mental Wellbeingmentioning
confidence: 99%
“…The remaining 32 studies assessed outcomes considered to be aspects of mental wellbeing, such as quality of life, life satisfaction, and affect, but did not report both hedonic and eudaimonic wellbeing. The WHO-5 Well-Being Index, used in 2 studies [ 48 , 70 ], asks how frequently individuals have felt “cheerful and in good spirits” and “calm and relaxed”, over the previous 2 weeks, but focusses on hedonic rather than eudaimonic wellbeing [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Benefits include increased birthweights [31][32][33]; lower mortality levels in greener neighborhoods [34,35], reduced stress levels, indicated by hormones such as cortisol [36,37], reduced heart disease [38], and lower levels of diabetes [39]. Human health benefits are likely to be higher in ecologically richer environments [40,41].…”
mentioning
confidence: 99%